Audit Internal dan Efektivitas Pengendalian Intern Penjualan - Radhi Abdul Halim Rachmat; Ivan Gumilar Sambas Putra; Ii Halilah (Jurnal Riset Bisnis dan Investasi, 2017)
Sales activity plays an important role and needs to be controlled because it affects to the revenue. Sales control requires sales analysis that reveal undesirable developments need to be corrected. Internal Auditors who are not directly involved in operational activities can, therefore, assess all activities. Internal Auditors also provides objective information regarding sales data that will be the basis for management decision making. The purpose of this study is to: determine whether the internal audit on sales activities conducted by the company has been done adequately; determine whether the internal control over sales has been implemented effectively; and determine the role of internal audit in supporting the effectiveness of internal control sales. The authors perform hypothesis testing by doing descriptive analysis and statistical analysis. Based on the results, the effectiveness of internal control can be explained by the Internal Audit role of 63.2%.